Approaching ultra-low thermal conductivity in β-SiC nanoparticle packed beds through multiple heat blocking mechanisms. (February 2017) - Wan, Peng; Gao, Liyin; Wang, Jingyang
Abstract: The crucial challenge for oxide thermal insulators, such as Al2 O3 and SiO2 nano-particle aggregates, is to solve the trade-off between extremely low thermal conductivity and unsatisfied sintering stability. We herein report the ultra-low thermal conductivities (0.068–0.1 W m − 1 K − 1 ) of β-SiC nanoparticle ( 35 nm) packed beds. The breakthrough is realized by multiple heat blocking mechanisms in the nanostructures. The samples also possess good thermal stability as high as 1500 °C. Our results provide a new strategy to explore ultra-low thermal conductivity materials with excellent thermal stability, regardless of their high intrinsic lattice thermal conductivities. Graphical abstract: